Sobre la posible etiología de la enfermedad celíaca - Rossi, Rodolfo (1937)
The authors report the case of a patient-of 19 years of age, with complete clinical studies and the examination of Morbid anatomy. Since the era of Samuel Gee, who discovered the disease, little has been added to its clinical picture. The etiology, symptomatology, and pathogenesis of the disease are reviewed. As in this case which motivated us to publish, large quantities of mycosis are found in the excrements, which are identified as Monilia albicans. This indicates the suitability of making a systematic search for fungus in celiac disease.